A phase I clinical trial assessing the safety, tolerability, and pharmacokinetics of inhaled ethanol in humans as a potential treatment for respiratory tract infections - Hancock, David G.; Ditcham, William; Ferguson, Eleanor; Karpievitch, Yuliya V.; Stick, Stephen M.; Waterer, Grant W.; Clements, Barry S. (Frontiers in Medicine, 2024)
Background: Current treatments for respiratory infections are severely limited. Ethanol’s unique properties including antimicrobial, immunomodulatory, and surfactant-like activity make it a promising candidate treatment for respiratory infections if it can be delivered safely to the airway by inhalation. Here, we explore the safety, tolerability, and pharmacokinetics of inhaled ethanol in a Phase I clinical trial. Methods: The study was conducted as a single-centre, open-label clinical trial in eighteen healthy adult volunteers, six with no significant medical comorbidities, four with stable asthma, four with stable cystic fibrosis, and four active smokers. A dose-escalating design was used with participants receiving three-dosing cycles of 40%, 60%, and then 80% ethanol v/v in water, 2 hours apart in a single visit. Ethanol was nebulised using a standard jet nebuliser, delivered through a novel closed-circuit reservoir system, and inhaled nasally for 10 minutes then orally for 30 minutes. Safety assessments included adverse event and vital sign monitoring, blood alcohol concentrations, clinical examination, spirometry, electrocardiogram, and blood tests. Results: No serious adverse events were recorded. The maximum blood alcohol concentration observed was 0.011% immediately following 80% ethanol dosing. Breath alcohol concentrations were high (median 0.26%) following dosing suggesting high tissue levels were achieved. Small transient increases in heart rate, blood pressure, and blood neutrophil levels were observed, with these normalizing after dosing, with no other significant safety concerns. Fifteen out of eighteen participants completed all dosing cycles with three not completing all cycles due to tolerability. The closed-circuit reservoir system significantly reduced fugitive aerosol loss during dosing. Conclusion: These data support the safety of inhaled ethanol at concentrations up to 80%, supporting its further investigation as a treatment for respiratory infection.